Pengaruh Kecerdasan Emosional Terhadap Prestasi Belajar Matematika Siswa Kelas V Sekolah Dasar Negeri 1 Manonjaya - Titing Sulastri; Syarip Hidayat; Yusuf Suryana (ABMAS, 2021)
This study aims to determine the effect of emotional intelligence on mathematics learning achievement of fifth grade students at SD Negeri 1 Manonjaya. The hypothesis tested is: there is an influence of emotional intelligence on mathematics learning achievement of fifth grade students at SDN 1 Manonjaya. The population in the study used all fifth grade students in Manonjaya 1 Elementary School, totaling 41 students consisting of 21 VA class students and 20 VB class students. This type of research is ex post facto. The approach in this study uses a quantitative approach. The independent variable in this study is emotional intelligence while mathematics learning achievement is the dependent variable. Data was collected using emotional intelligence questionnaires and documentation of mathematics learning achievement. Data analysis technique is done by using descriptive analysis and inferential analysis with simple regression analysis techniques. Descriptive analysis results show that the level of emotional intelligence of students in general is included in the moderate category with a percentage of 63.4%. While the description of student mathematics learning outcomes in general are included in the moderate category with a percentage of 61.0%. From the results of inferential analysis using simple linear regression, the equation Y = 70.636 + 0.081X was obtained. From the significant test results obtained a significant value of 0.028 where a significant value 0.05 (0.028 0.05), thus Ha is accepted and Ho is rejected. The conclusion of this study is that there is an influence of emotional intelligence on mathematics learning achievement.